آلية تمويل وتسيير الصندوق الوطني للضبط والتنمية الفلاحية - حسينة, حوحو; سعاد, حوحو (Sciences humaines; Vol. 23 (2011): SCIENCES HUMAINES, 2014)
لقد قامت الجزائر في مطلع القرن الحالي بوضع برنامجا شاملا للتنمية الفلاحية، يهدف إلى تحسين الإنتاج الفلاحي كما ونوعا وذلك تحضيرا لاندماج الفلاحة الجزائرية في المحيط العالمي، بالإضافة إلى أهداف أخرى اقتصادية اجتماعية وسياسية . ويمول هذا البرنامج مجموعة من الصناديق أهمها الصندوق الوطني للضبط والتنمية الفلاحية الذي يدعم معظم النشاطات الفلاحية. وسنحاول من خلال هذا البحث التعرف على هذا البرنامج والآلية التي يتم بها تمويل وتسيير هذا الصندوق وكذا النشاطات التي يدعمها .   By the beginning of the current century, Algeria has set up a comprehensive national programme for agricultural development, which aims at improving the quantity and quality of farming production, for the purpose of integrating Algerian agriculture into the global environment, also it has other economic, social and political objectives.  This programme has financed by many funds, the most important one, is the (FNRDA) national fund for regulation and agricultural development, this latter has subsidized most of agricultural activities. I'll try to recognize the mechanism of financing and managing this fund to gather with its subsidized activities.